Analysis of semiconductor manufacturing process for performance improvement - Guo, Xiangyu (2017)
Variability is the greatest enemy of a manufacturing system, which causes unstable performances and varies the productivity. This report focuses on reducing the variability and improving the performance of a semiconductor manufacturing process. Other methods to improve the performance of a semiconductor manufacturing process includes improving machine's process time, standard work of operators and other ergonomics factors; these are included in this study. A simulation model of the manufacturing semiconductor cell was created using the Arena software. It was based on actual production process data from the author's company Heptagon. To get different performances of the manufacturing system, some scenarios of variations had been applied on the simulation model. The results were used in further analysis and discussion to investigate the factors that produce the best improvement or cause the worst productivity in the manufacturing system. The author proposed a set of solutions to improve the performance of the semiconductor manufacturing system. These include improvements on number of operators, walking speed of operators, process analysis time reduction and machine modification time reduction.